2019
DOI: 10.28985/jsc.v8i1.504
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reproducibility of commercial cycling power meters in hot and cold environmental temperatures

Abstract: Power meters are a training tool used to help cyclists improve performance by objectively monitoring intensity.  Some power meters are well established and validated, whereas others are relatively new.  Most power meters have been tested for validity and reliability in laboratory and field settings of similar conditions; however, the reproducibility of these power meters across different temperatures has not been established. To examine the potential differences of the CompuTrainer, PowerTap, Stages, and Vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The second variable was the highest mean power that the cyclist held for a given period (i.e., twelve periods from 1 s to 60 min). Additionally, critical power, which was defined as the power asymptote of the hyperbolic relationship between power output and time to exhaustion [ 9 ], was also obtained from the power output profile, as previous studies did [ 6 ]. Finally, Normalized power, defined as the power output the cyclist could sustain if intensity were maintained constant without any variability [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second variable was the highest mean power that the cyclist held for a given period (i.e., twelve periods from 1 s to 60 min). Additionally, critical power, which was defined as the power asymptote of the hyperbolic relationship between power output and time to exhaustion [ 9 ], was also obtained from the power output profile, as previous studies did [ 6 ]. Finally, Normalized power, defined as the power output the cyclist could sustain if intensity were maintained constant without any variability [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, Maier et al [ 3 ] observed that the power output registered by different power meters is highly variable (even when they have been designed by the same manufacturer) and recommend further studies in field conditions with changes in ambient temperature, vibrations, or gear shifts. Shute et al [ 6 ] observed that environmental temperature affected the registry of various power meters. Furthermore, Bouillod et al [ 5 ] demonstrated that vibration and field conditions affect the power output measured.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Gardner, Stephens, Martin, Lawton, Lee, and Jenkins [ 42 ] stated that both the SRM and PowerTap power meters are sensitive to differences in temperature. More recently, Shute et al [ 178 ] compared four systems (CompuTrainer, PowerTap Hub, Stages crank, and Garmin vector) in three different environmental conditions of temperature, cold 7°, regular 20°, and hot 33°. In this study, the authors observed a significant alteration of accuracy for PowerTap, Vector, and Stages, especially in the hot situation.…”
Section: Discussionmentioning
confidence: 99%